STRATEGI DAN TANTANGAN MANAJEMEN TEKNOMEDIA DI LEMBAGA PENDIDIKAN ANAK USIA DINI - Mega Suteki; Retno Wuri Sulistyowati (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
Digital learning media management is a crucial skill required by the heads of educational institutions to navigate the digital era. This research aims to depict: (1) the challenges faced by the leaders of Early Childhood Education (PAUD) institutions in Merauke City in managing technomedia in the learning process, and (2) the strategies employed by these leaders to overcome challenges in technomedia management during the learning process. The informants for this study were purposefully sampled from school principals in Merauke City. The primary challenges confronted by school principals in managing digital learning media in Early Childhood Education institutions (PAUD) include the availability of adequate technological resources, the development of teachers' skills in using technology, and the management of student data security and privacy. School principals also need to take into account parental involvement in supporting the use of digital media at home and ensure that technology use remains balanced with the physical and social activities of children. To tackle these challenges, strategies employed by school principals include organizing training and developing teachers' skills in technology use, selecting quality digital learning content, and establishing clear policies and guidelines related to technology use. Additionally, careful monitoring of students' technology use and maintaining a balance between technology use and traditional learning experiences are also emphasized. By implementing these strategies, PAUD school principals can effectively manage digital learning media, enhance the quality of early childhood education, and ensure that technology is used judiciously in the learning process.